Internal auditing in plain english : a simple guide to super effective ISO audits - Cochran, Craig (Chico, CA : Paton Professional, 2017)
A successful internal audit program is essential to the success of any management system. A successful internal audit program also requires successful auditors. Auditing isn$1 (Bt taught in school and doesn$1 (Bt always come easily to those just starting out. Fortunately, bestselling author Craig Cochran has distilled down the essential elements of a successful internal audit program into plain English that anyone can understand. Just as he did with his bestselling ISO 9001:2015 in Plain English book, Cochran has written a comprehensive yet easily understandable guide to internal auditing. Internal Auditing in Plain English was written so that anyone at any level of the organization can understand the basics of a successful internal auditing process. Plus, the book goes beyond the basics with comprehensive detail about establishing an internal audit program, selecting and training auditors, auditing requirements, interview techniques, planning audits, reporting, audit follow ups, and much more. This straightforward book is ideal for people who are new to internal auditing, experienced auditors who want to get more out of their audits, and for employees who just need a basic understanding of what internal auditing is and how it applies to them. Cochran uses real-world examples and frequently asked questions to help build a comprehensive understanding of a successful internal audit program and to build the skills of successful internal auditors.s
Keywords: AUDITING, INTERNAL